2015
DOI: 10.1007/s13277-015-3677-7
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy clustering demonstrates that codon 72 SNP rs1042522 of TP53 gene associated with HNSCC but not with prognoses

Abstract: It is estimated that 7.6 million people will die as a consequence of head and neck squamous cell carcinoma (HNSCC). Genetic predisposition has emerged as an important risk factor in the development and prognosis of HNSCC. Considering this, the aim of the current study is to assess whether codon 72 SNP of the TP53 gene (rs1042522) is associated with an increased odds ratio of developing HNSCC or with a worse prognosis in patients with HNSCC. Analysis of the rs1042522 in HNSCC patients and in control individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Neither P16 nor p53 expression was an independent risk factor affecting the prognosis of laryngeal cancer. This is consistent with previous studies [20,21].…”
Section: Discussionsupporting
confidence: 94%
“…Neither P16 nor p53 expression was an independent risk factor affecting the prognosis of laryngeal cancer. This is consistent with previous studies [20,21].…”
Section: Discussionsupporting
confidence: 94%
“…These comparisons indicate that Arg substitution at codon 72 may be a risk factor for HNC in South-Asian populations. However, this observation is in contrast to the previous studies, which imply that Pro72 in p53 may be associated with increased risk to cancers (Cao et al, 2020, Lotfi Garavand et al, 2020, Pinheiro et al, 2015, Cortezzi et al, 2004. This contradiction may be partially explained by other genetic and/or environmental factors, which have not been considered in the present discovery study.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, this arginine form of the gene product p53 has been shown to be more susceptible to HPV16 E6 mediated degradation than the proline form [35]. In addition, the arginine form of p53 was found to be associated with HNSCC, but not with worse prognosis of the disease [36]. Furthermore, Habbous et al reported in a meta-analysis that the arginine variant of p53 was associated with progression of squamous intraepithelial lesions to cervical cancer only in the presence of HPV positivity [37].…”
Section: Discussionmentioning
confidence: 99%